Gharar; Konsep dan Penghindarannya pada Regulasi Terkait Screening Criteria di Jakarta Islamic Index - Agus Triyanta (Fakultas Hukum Universitas Islam Indonesia, 2010)
One of the main aspects that distinguishes a convensional capital market and a syariah capital market is whether there is or is not the speculative element or, in the Islamic law terminology, known as gharar, in the offered business instrument. This research is meant to reveal on how the gharar concept in Islamic financial law, as well as how the concept being implemented in Screening Criteria in Jakarta Islamic Index (JII), Indonesian syariah capital market. This research has compiled different kinds of data in the form of norm and regulation both from Islamic law and governmental institution which is responsible to the capital market. The data, then, was analyzed qualitatively through interpretation. The result has concluded that generally, gharar found in Islamic law, is meant that ther is a hidden element which could cause a disadvantage or a danger from the involving side in a transaction while the syariah criteria for the screening process of JII has two aspects; a company in JII is the company that does not have a business related to the transaction of ribawi, gharar, and gambling (maysir). Second, the transaction done in JII must be fulfilled the principle of fully care (ihtiyath), not speculative or manipulative (dharar, gharar, riba, maisir, rishwah, and kezaliman/tyranity).Key words : Gharar, screening criteria